Дослідження південної частини Верхнього міста Ольвії у 2009 р. - Крапівіна, В.В.; Буйських, А.В.; Хмелевський, Д.М. (Археологічні дослідження в Україні, 2010)
The publication acquaints with the main results of 2009 research at the southern part of the Upper City of Olbia: at the areas P-19, P-25, and the Northern defensive wall of the citadel.